PENGARUH LEVERAGE, FIRM SIZE DAN NET WORKING CAPITAL TERHADAP CASH HOLDING - Romel, William; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2025)
The discussion in this research was carried out in order to know if leverage, firm size, and net working capital has an effect to cash holding in consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) for the 2019 – 2021 period. The research used 62 samples and 186 data which were selected using purposive sampling. Research data were processed using Eviews 12. Based on the result of data processing, firm size has. Meanwhile, leverage and net working capital have a negative effect on cash holding.